Losing work, moving away? Regional mobility after job loss - Daniel Fackler; Lisa Rippe (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
Using German survey data, we investigate the relationship between involuntary job loss and regional mobility. Our results show that job loss has a strong positive effect on the propensity to relocate. We also analyze whether the high and persistent earnings losses of displaced workers can in part be explained by limited regional mobility. Our findings do not support this conjecture as we find substantial long lasting earnings losses for both movers and stayers. In the short run, movers even face slightly higher losses, but the differences between the two groups of displaced workers are never statistically significant. This challenges whether migration is a beneficial strategy in case of involuntary job loss.
urn:nbn:de:gbv:3:2-60724
Keywords: J61; J63; 330; job displacement; plant closure; regional mobility; earnings; SOEP